Genealogía híbrida de las activistas jóvenes en Argentina: “Muchas disidencias y muchos feminismos” - Jay Friedman, Elisabeth; Rodríguez Gustá, Ana Laura (European Review of Latin American and Caribbean Studies, 2024)
Abstract: The hybrid genealogy of young women activists in Argentina: “Many dissidences and many feminisms”Feminist mobilizations have intensified in Latin America thanks to the incorporation of a significant youth contingent. These new activists bring with them transformations in social movements’ strategies and frameworks of understanding. Taking the Argentine case as the context, in this article we focus on a fundamental dimension of young women’s feminist imagination: who they consider influential movement figures. Based on a qualitative study, we reconstruct a feminist genealogy from the perspective of a new generation of activists. Their movement genealogy, according to our findings, combines figures from diverse trajectories of struggle and sites of activism, with heterogeneous positions regarding feminism. Furthermore, in this genealogy, the young women themselves play a central role. ResumenLa movilización feminista se ha intensificado en América Latina gracias a la incorporación de un importante contingente juvenil. Estas nuevas activistas traen consigo transformaciones en los marcos de sentido y en las estrategias de los movimientos sociales. Tomando Argentina como contexto de estudio, este artículo aborda una dimensión fundamental del imaginario feminista de las jóvenes: a quién consideran antecesoras en la construcción del movimiento e inspiradoras para su propias biografías feministas. Mediante un estudio cualitativo, se muestra que las nuevas generaciones reconstruyen una genealogía híbrida que combina figuras prove-nientes de diversas trayectorias de lucha y sitios de activismo, con posiciones heterogéneas respecto del feminismo. Además, en esta genealogía, las propias jóvenes se colocan en un papel protagónico y no como meras herederas de espacios construidos por predecesoras.